THE INFLUENCE OF SELF EFFICACY, INTERNAL COMMUNICATION, AND INNOVATIVE WORK BEHAVIOR ON EMPLOYEE PERFORMANCE AT PUBLIC WORKS AND SPATIAL PLANNING PROVINCE NORTH SUMATERA - Padilah Rahmi Lubis; Anggia Sari; Sari Wulandari; Toni Hidayat (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to determine and analyze the effect of Self Efficacy, Internal Communication, and Innovative Work Behavior on Employee Performance of the Public Works and Spatial Planning Office of North Sumatra Province. The method used is descriptive quantitative with a sample of 66 planning section employees. Data collection techniques were carried out through observation, documentation, and questionnaires using a Likert scale. Data analysis includes validity, reliability, classical assumption, and multiple linear regression tests. Hypothesis testing was carried out with the t test, F test, and coefficient of determination (R²), using the help of IBM SPSS 26 software. The results showed that partially, Self Efficacy (X1), Internal Communication (X2), and Innovative Work Behavior (X3) had a significant effect on Employee Performance (Y). With the t-test Self Efficacy (X1) obtained a t-count value of 6.943 > t-table of 1.669, Internal Communication (X2) obtained a t-count value of 4.532 > t-table of 1.669, and Innovative Work Behavior (X3) obtained a t-count value of 3.401 > t-table of 1.669. The F test shows the F-count value of 28.202 > Ftable 2.75 with a significance of 0.000. The coefficient of determination (R²) value of 57.7% of the Employee Performance variable can be explained by the Self Efficacy, Internal Communication, and Innovative Work Behavior variables while the remaining 42.3% is explained by other variables outside the variables studied.